(untitled) (Baghdad Science Journal, 2023)
The current study uses the flame fragment deposition (FFD) method to synthesize carbon nanotubes (CNTs) from Iraqi liquefied petroleum gas (LPG), which is used as a carbon source. To carry out the synthesis steps, a homemade reactor was used. To eliminate amorphous impurities, the CNTs were sonicated in a 30 percent hydrogen peroxide (H2O2) solution at ambient temperature. To remove the polycyclic aromatic hydrocarbons (PAHs) generated during LPG combustion, sonication in an acetone bath is used. The produced products were investigated and compared with standard Multi-walled carbon nanotube MWCNTs (95%), Sigma, Aldrich, using X-ray diffraction (XRD), thermo gravimetric analysis (TGA), Raman spectroscopy, scanning electron spectroscopy (SEM), Energy Dispersive X-ray Spectroscopy (EDS) and Transmission Electron Microscopy (TEM). Under the applied experimental circumstances, the obtained characterization data confirm the synthesis of multi-wall carbon nanotubes (MWCNTs) with portion from few wall carbon nanotubes (FWCNTs). The average diameter of synthesized Carbon nanotubes ranged from 31.26 to 78.00 nm, with a purity of more than 65 percent.